The Role of Existing and Newer Calcium Channel Blockers in the Treatment of Hypertension - Basile, Jan (J Clin Hypertens (Greenwich), 2007)
Calcium channel blockers (CCBs), which include both dihydropyridines such as nifedipine and amlodipine and non‐dihydropyridines (verapamil and diltiazem), are among the most widely prescribed agents for the management of essential hypertension. Several large outcome risk trials and comprehensive meta‐analyses have found that CCBs reduce the cardiovascular morbidity and mortality associated with uncontrolled hypertension, including stroke. CCBs, however, appear less effective than angiotensin‐converting enzyme inhibitors and diuretics for preventing heart failure and myocardial infarction. CCBs are among the agents listed as potential first‐line therapy, either alone or in combination with other agents in hypertension management guidelines. Furthermore, CCBs are suitable for add‐on therapy in combination with diuretics, angiotensin‐converting enzyme inhibitors, and angiotensin‐II receptor blockers. CCBs may be partially suitable for patients with comorbid Raynaud's syndrome, isolated systolic hypertension (dihydropyridine), or angina pectoris (non‐dihydropyridine). The newer inherently long‐acting dihydropyridine agents (e.g., lacidipine, lercanidipine), which are not currently available in the United States, appear to have comparable efficacy to older agents of the dihydropyridine class but may have an improved tolerability profile, especially with regard to peripheral edema.